Effects of tributary floodplain on confluence hydrodynamics - Yuan, Saiyu; Yan, Guanghui; Tang, Hongwu; Xiao, Yang; Rahimi, Hamidreza; Aye, Moe Nandar; Gualtieri, Carlo (Journal of hydraulic research, 2023)
Confluences are common components of river networks and are characterized by a highly complex flow structure. Two confluence geometries, without and with the floodplain in the tributary, were comparatively investigated to highlight the effects of floodplain on confluence hydrodynamics. The three-dimensional velocity field and the spatial distribution of turbulent kinetic energy and Reynolds shear stresses were analysed. In the second geometry, a tilted shear layer was observed, which was related to the flow expansion from the main channel into the tributary. Significant secondary motions are mainly related to the fluid upwelling in the lee of the floodplain step and streamline curvature. A wider flow separation zone was found, while the length of the separation zone was not affected by the floodplain flow. The results could be useful to understand the complex hydrodynamics of the large confluence between the Yangtze River and the Poyang Lake, characterized from a floodplain under high flow conditions.